Book Review: Kalam and its Relevance in the Muslim Scholarship of Religion: An Integrated Approach - Mohamed Ashath (MAQOLAT: Journal of Islamic Studies, 2025)
Kalᾱm and Its Relevance in the Muslim Scholarship of Religion is both an academic intervention and a theological invitation. It calls on Muslim scholars to reclaim their rich heritage of reasoned faith, to revisit the tools of Kalᾱm with renewed vigour, and to engage with other religious traditions not from a place of insecurity but from a confident and principled commitment to truth. This book is a must-read for scholars of Islamic theology, students of comparative religion, and anyone concerned with interfaith dialogue. It bridges the gap between Usul al-Din, Kalᾱm and modern religious studies, not by diluting Islamic principles but by reaffirming their relevance in a world that desperately needs more principled, informed, and compassionate conversations across faiths.